Effect of matrix metalloproteinase-inhibiting solutions and aging methods on dentin bond strength - Perote, Letícia C.C. Costa [UNESP]; Kamozaki, Maria Beatriz Beber [UNESP]; Gutierrez, Natália C. [UNESP]; Tay, Franklin R.; Pucci, Cesar R. [UNESP] (My University, 2015)
Purpose: This study examined the effects of matrix metalloproteinase-inhibiting solutions and aging methods on the bond strength between resin composite and human dentin. Materials and Methods: Crown segments of 105 human non-carious molars were bonded using simulated pulpal pressure at 20 cm water pressure. The teeth were randomly split into 5 groups according to the solution applied: CG (control, no solution), CHX (0.2% chlorhexidine), EPE (10% ethanolic propolis extract), APE (aqueous propolis extract), and E (70% ethanol). Each solution was left on the acid-etched dentin for 1 min. Adper Single Bond 2 and resin composite (Filtek Z350 XT) were applied to all specimens. The 5 groups were subdivided according to the aging method: SI (sectioned immediately); S (storage in artificial saliva for 6 months); and T (thermomechanical aging with 240,000 mechanical cycles and 1000 thermal cycles). Specimens were sectioned into sticks and subjected to microtensile testing. Bond strength data were analyzed by two-factor ANOVA followed by a post-hoc Tukey's test (α = 0.05). Results: For the factor solution, there was no significant difference among the groups (p = 0.32). For the factor aging method, significant differences were found (p < 0.001), with the following mean bond strengths (MPa): SI: 31.1; S: 24.4; T: 26.8. Conclusions: The use of matrix metalloproteinase-inhibiting solutions on dentin as an adjunct to the application of an etch-and-rinse adhesive does not prevent the loss of bond strength after aging. Nevertheless, these solutions have no adverse effect on adhesion to tooth structure.
Keywords: Aging; Matrix metalloproteinase; Resin composite; Tensile strength